2014
DOI: 10.1007/s00264-014-2291-4
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of trochlear dysplasia in anterior cruciate ligament tears

Abstract: Purpose The purpose of the present epidemiologic study is to record the radiographic presence of trochlear dysplasia and patella alta in patients who undergo anterior cruciate ligament (ACL) reconstruction as a potential underlying factor for postoperative anterior knee pain (AKP). Methods All consecutive cases of skeletally-mature ACLdeficient knees that would undergo ACL reconstruction in three different hospitals were prospectively included during a six-month period. Inclusion criteria were acute and subacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 52 publications
3
29
1
Order By: Relevance
“…22 Impaired trochlear morphology is increase the risk of early osteoarthritis following ACL reconstruction. 23 In 2014, Ntagiopoulos et al 6 attempted to record the incidences of both patella alta and trochlear dysplasia, which are the main patellofemoral disorders in patients who undergo ACL reconstructions, in a study of 299 patients using direct X-rays and the Caton-Deschamps index. They found 14.7% trochlear dysplasia and 5% patella alta, and they revealed that these could be possible additional risk factors for postoperative anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Impaired trochlear morphology is increase the risk of early osteoarthritis following ACL reconstruction. 23 In 2014, Ntagiopoulos et al 6 attempted to record the incidences of both patella alta and trochlear dysplasia, which are the main patellofemoral disorders in patients who undergo ACL reconstructions, in a study of 299 patients using direct X-rays and the Caton-Deschamps index. They found 14.7% trochlear dysplasia and 5% patella alta, and they revealed that these could be possible additional risk factors for postoperative anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…disrupting the knee extension and flexion. 5,6 Two of the major morphological abnormalities that cause patellar instability are patella alta and trochlear dysplasia. Patella alta, or a "high-riding" patella, refers to a patella localized at a higher level above the trochlear fossa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The control group consisted not of asymptomatic volunteers but of patients evaluated for other injuries or conditions. Although previous studies have used similar control populations, possible confounding variables may exist, as highlighted by Ntagiopoulos et al, 22 who reported an increased prevalence of trochlear dysplasia and patella alta in patients sustaining anterior cruciate ligament injuries. Despite this, only 2 patients in the control group with a primary diagnosis of anterior cruciate ligament injuries were classified as having trochlear dysplasia.…”
Section: (96%)mentioning
confidence: 99%
“…In addition, we analyzed a superior number of specimens with good to excellent intra-and interrater reliability. In another study, Ntagiopoulos et al 24 investigated the prevalence of the trochlear dysplasia in 299 patients with anterior cruciate ligament (ACL) ruptures and reported it to be 14.7% (44 patients). The trochlear dysplasia was classified as type A in 93% and type C in 7% of patients.…”
Section: Discussionmentioning
confidence: 99%